Pemberdayaan Peternak dalam Usaha Penggemukan Sapi Potong di Desa Kenteng, Kecamatan Nogosari, Kabupaten Boyolali - Shanti Emawati; Sudiyono Sudiyono; Sutrisno Hadi Purnomo; Suwarto Suwarto; Ayu Intan Sari; Endang Tri Rahayu (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2020)
Domestic beef supply is fulfilled by farmers from Kenteng Village, Nogosari Sub-district, Boyolali Regency. Farmers in Kenteng Village develop beef cattle business by forming a beef cattle farmers' groups Sumber Makmur, Taruban Mulyo and Ngudi Mulyo. The problem faced by farmers in Kenteng Village is that the business of beef cattle fattening is not optimal. The purpose of this activity is to empower beef cattle farmers who are members of the livestock farmer groups in Kenteng Village. The method of taking location and respondent in this activity is purposive sampling. This activity methods include Focus Group Discussion (FGD), extension and training activities through the preparation of feed rations and fermented rice straw. The result of this activity is the empowerment of farmers in the business of beef cattle fattening through the implementation of counseling and training for the preparation of ration formulations and fermented straw making in Kenteng Village, which is seen as being more empowered because the farmers' knowledge increases and the feed tested on livestock can be consumed properly so that livestock performance increases. The conclusion of this activity is that farmers become more empowered due to increased farmer knowledge and the feed tested on livestock can be consumed properly, thereby increasing livestock performance.